Continuous practice of conservation agriculture for 3-5 years in intensive rice-based cropping patterns reduces soil weed seedbank - Hossain, Mohammad Mobarak; Begum, Mahfuza; Hashem, Abul; Rahman, Md. Moshiur; Haque, Md. Enamul; Bell, Richard W. (MDPI, 2021)
When farmers first shift from conventional tillage (CT) to conservation agriculture (CA) practices, the control of weeds may be more difficult, due to the absence of tillage. However, continuous CA, over several years, may alter the weed seedbank. The nature of the weed seedbank changes over time, in intensively cropped rice-based rotations that are typical of the Eastern Gangetic Plain, are not well understood. Two on-farm CA experiments were sampled (in Beluapara after 3 years and Digram after 5 years) in Bangladesh for the effects of strip planting (SP) and bed planting (BP) at both the sites, plus no-tillage (NT) in Beluapara, and increased retention of the residue of previous crops (20% vs. 50%). The conventional tillage (CT) and 20% residue was the control treatment. The weed seedbank in 0–15 cm soil was quantified by assessing the emergence of weeds from soils collected from the field after irrigation, (Boro) rice in Digram and wheat in Beluapara, and they were allowed to emerge in trays in a shade-house experiment. The year-round count of emerged weeds at both the locations revealed the fewest number of weed species (especially broadleaf weeds), and the lowest weed density and biomass in SP, followed by CT, BP, and NT, with 50% crop residue mulch. Relative to CT, the SP, BP, and NT produced relatively more perennials weeds, as follows: Alternanthera denticulata ((R.) Brown.), Cyperus rotundus (L.), Dentella repens (L.), Jussia deccurence (Walt.), Leersia hexandra (L.), and Solanum torvum (Sw.), which was the opposite of CT that was enriched with the following annual weeds: Cyperus iria (L.), Digitaria sanguinalis (L.), Euphorbia parviflora (L.), Fimbristylis miliacea (L.), Lindernia antipoda (L.), L. hyssopifolia (L.), and Monochoria hastata (L.). The soil weed seed bank reduced by 13% in SP, while it increased by 19% and 76% in BP and NT, respectively, compared with CT. The species diversity reduced in SP and NT, by 24% and 11%, respectively, but increased by 2% in BP. In 50% residue, the soil weed seed bank and species diversity reduced by 16% and 14%, respectively, relative to that of 20% residue. The continuous practice of CA, for 3 or more years, in two rice-based crop rotations, decreased the size of the weed seedbank, but increased the relative proliferation of specific perennial weeds.